A Geotechnical Database for Utah (GeoDU) enabling quantification of geotechnical properties of surficial geologic units for geohazard assessments. Issue 1 (February 2020) - Sharifi-Mood, Mahyar; Gillins, Daniel T.; Olsen, Michael J.; Franke, Kevin W.; Bartlett, Steven F.
Geotechnical borehole information is often used for liquefaction hazard mapping, but can be highly variable in terms of quantity and quality. In addition, geotechnical borehole logs are often provided as images in reports rather than delivered in a structured, queryable database, which makes the logs and supplementary information difficult to organize particularly across a large geographic area. In contrast, surficial geologic mapping is generally available and often accessible in geographic information systems (GIS) format. This article's objective is to describe the compilation of a geotechnical database for regional mapping purposes and to demonstrate the value of documenting geotechnical data into a consistent data format. Specifically, this article describes the development of three geotechnical borehole databases compiled in Utah, which has been coined the Geotechnical Database for Utah (GeoDU). The database is used to quantify geotechnical properties for subsequent liquefaction evaluations of surficial geologic units comprising similar depositional environment and age. The resulting GeoDU is an important resource for future efforts with many applications including community data sharing and planning for preliminary geotechnical site investigations.